1983
DOI: 10.1111/j.1471-4159.1983.tb13589.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteins of the Extracellular Fluid of Mouse Brain: Extraction and Partial Characterization

Abstract: An extraction procedure for the isolation of proteins from the brain extracellular fluid (ECF) was developed and applied to studies of the ECF components of mouse brain. Perfused intact brains were incubated in an isotonic medium for periods of up to 2 h at 0 degrees C to allow the release of ECF into the medium without disruption of the integrity of the tissue. The validity of the extraction procedure was established by (a) the fact that the total yield of ECF proteins was constant per unit weight of brain ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The following points illustrate how extracellular GAGs may affect brain physiology. Hofstein et al (1983) showed that the extracellular protein concentration in mouse brain was 20 times higher than in CSF and that very little protein of M, < 90,000 was detected. They suggested "the extracellular space has an even distribution throughout the cerebrum.…”
Section: Discussionmentioning
confidence: 98%
“…The following points illustrate how extracellular GAGs may affect brain physiology. Hofstein et al (1983) showed that the extracellular protein concentration in mouse brain was 20 times higher than in CSF and that very little protein of M, < 90,000 was detected. They suggested "the extracellular space has an even distribution throughout the cerebrum.…”
Section: Discussionmentioning
confidence: 98%
“…The supernatant was used for protein analysis with a BCA protein assay kit (Thermo Scientific, Waltham, MA) and for MPO activity assays. For separation of extra- (ECF) and intracellular protein fractions (ICF) we modified a method initially described for mouse brains [24]. We washed harvested organs (kidney, brain, liver, heart, spleen, and lungs) three times in PBS and incubated them for 2 hours in extraction buffer (0.32 M sucrose [Sigma], 1 mM CaCl 2 [Sigma], 10 U/ml Heparin [APP Pharmaceuticals, Schaumburg, IL] in Hanks Balanced Salt Solution [HBSS]).…”
Section: Methodsmentioning
confidence: 99%
“…The protocol of extracellular protein extraction was adopted from (Hofstein et al, 1983, Pulli et al, 2013). After cardiac perfusion with 20ml cold saline in an anesthetized mouse, brains were harvested and washed in PBS three time.…”
Section: Methodsmentioning
confidence: 99%